Socialismo cien años después = Socialism one hundred years later - Pérez Soto, Olga; Esquenazi Borrego, Arelys (Textos & Contextos (Porto Alegre))
The aim of this article is to claim the socialist imaginary in the face of the failure of capitalism and the mistakes of the different experiences of social transformation. One hundred years of the first socialist experience in the world, is taken as a motivation to reflect on the possible themes of the socialist science agenda; in the delimitation of the evaluation of socialism, as a monumental historical project, between the need for social change and how to do it